The characterization of tourmaline and its effects on plant growth - Sin-Yi Huang; Chun Ming Yu; Po-Yuan Liu; Yun-Hseng Yu; Chien Hung Chen; Ching Fung Liu; Yaju Juang (Sustinere: Journal of Environment and Sustainability, 2017)
The purpose of this study was to investigate the characteristics of ACERALIVEN™, a commercial tourmaline, and to evaluate its effects on plant growth. Our analysis indicates that ACERALIVEN™ belongs to the Si-Al-Mg tourmaline structure and contains trace metals such as zirconium, potassium, and iron. It is capable of emitting far-infrared energy with an emissivity of 0.829. When introduced into water, tourmaline increases the water's alkalinity. Additionally, it releases negative hydroxyl ions and dissolved oxygen, creating what is known as hydrogen water. Mung beans submerged in ACERALIVEN™-treated water exhibit a longer lifespan compared to those in untreated water. Furthermore, tourmaline can enhance plant growth by removing chlorine and emitting far-infrared radiation, which is beneficial for plant metabolism.